The impact of industry competition on the value relevance of goodwill impairments across different information environments - Sabri Boubaker (Journal of International Accounting, Auditing and Taxation, 2024)
Building upon prior studies that explore the impact of competition on financial reporting quality, this paper investigates the influence of industry-level competition on the value relevance of goodwill impairments. Additionally, it examines whether this impact is more pronounced for firms operating in countries with rich information environments. We analyze 21,224 firm-year observations from companies in 21 countries that reported under International Financial Reporting Standards (IFRS). We find that companies facing higher product market competition tend to report impairment losses that are relevant to investors’ equity valuation decisions. This is consistent with the notion that companies in competitive industries are subject to greater scrutiny and have fewer incentives to manipulate their impairment reporting. We also find that the impact of industry competition on the value relevance of goodwill impairments is more pronounced in the rich information environments of market-based economies than bank-oriented economies. These findings underscore the impact of competition and its interplay with the information environment on the market perception of accounting information that is subject to managerial discretion.